CONSTRUCTION OF PRODUCTIVE AGEING: BIOLOGICAL, PSYCHOLOGICAL AND ENVIRONMENTAL FACTORS - OLGA YU. STRIZHITSKAYA; MARINA D. PETRASH (Консультативная психология и психотерапия, 2022)
Introduction. The construction of old age is a set of strategies to create and implement the image of the desired old age. The article considers biological, psychological and environmental factors from the point of view of their modeling, which lend themselves to the possibility of creating, managing and eliminating certain mechanisms, depending on their role in the structure of aging. Objective. The work is devoted to systematization of scientific data on aging and the mechanisms of maintaining the quality of life during the aging period. The article examines biological, psychological, social and environmental factors that affect the specifics of aging. Methods. Theoretical analysis of modern research in the field of the psychology of aging. Results and conclusions. It has been shown that genetic and physiological mechanisms are not unconditional predictors of aging, but can be modified. At the same time, psychological and social factors lend themselves only to conditional modeling. The most flexible at this stage are various environmental factors that make it possible to significantly correct aging trends. The analysis showed that the factors and mechanisms known at this stage can be conditionally divided into modeled, conditionally modeled and difficult to model. At the same time, among such factors, conditional and easily modeled ones prevail, which allows us to develop the idea of construction of aging at earlier stages. The data indicate that the mechanisms of subjectivity underlie the possibilities of constructing aging, and the basis for the formation of strategies is adequate and positive representations of one’s own aging.